Retrospectively Assessed Muscle Tone and Skin Colour following Airway Suctioning in Video-Recorded Infants Receiving Delivery Room Positive Pressure Ventilation - Gazmend Berisha; Anne Marthe Boldingh; Britt Nakstad; Elin Wahl Blakstad; Arild Erland Rønnestad; Anne Lee Solevåg (MDPI AG, 2023)
Background: Recently, the International Liaison Committee on Resuscitation published a systematic review that concluded that routine suctioning of clear amniotic fluid in the delivery room might be associated with lower oxygen saturation (SpO2) and 10 min Apgar score. The aim of this study was to examine the effect of delivery room airway suctioning on the clinical appearance, including muscle tone and skin colour, of video-recorded term and preterm infants born through mainly clear amniotic fluid. Methods: This was a single-centre observational study using transcribed video recordings of neonatal stabilizations. All infants who received delivery room positive pressure ventilation (PPV) from August 2014 to November 2016 were included. The primary outcome was the effect of airway suctioning on muscle tone and skin colour (rated 0-2 according to the Apgar score), while the secondary outcome was the fraction of infants for whom airway suction preceded the initiation of PPV as a surrogate for "routine" airway suctioning. Results: Airway suctioning was performed in 159 out of 302 video recordings and stimulated a vigorous cry in 47 (29.6%) infants, resulting in improvements in muscle tone (p = 0.09) and skin colour (p < 0.001). In 43 (27.0%) infants, airway suctioning preceded the initiation of PPV. Conclusions: In this single-centre observational study, airway suctioning stimulated a vigorous cry with resulting improvements in muscle tone and skin colour. Airway suctioning was often performed prior to the initiation of PPV, indicating a practice of routine suctioning and guideline non-compliance.